Stability of black grass jelly (Mesona chinensis) probioticated by encapsulation of Lactobacillus plantarum Mar8 with agar and gum Arabic - NILAM FADMAULIDHA WULANDARI; TITIN YULINERY; NANDANG SUHARNA; NOVIK NURHIDAYAT (Smujo International, 2019)
Abstract. Wulandari NF, Yulinery T, Suharna N, Nurhidayat N. 2019. Stability of black grass jelly (Mesona chinensis) probioticated by encapsulation of Lactobacillus plantarum Mar8 with agar and gum Arabic. Nusantara Bioscience 11: 84-88. Black grass jelly [Mesona chinensis (Benth)] is one of the traditional food ingredients that can be used as the encapsulation material. However, syneresis easily occurs so that becomes a problem during storage. This study was conducted to evaluate the effect of type of stabilizers (agar and gum Arabic) and storage temperature (cold/4oC and ambient temperature/37oC) on black grass jelly stability and the viability of encapsulated Lactobacillus plantarum Mar8 in probiotication. The concentrations of stabilizers were 0.5%; 1.0%; 1.5% and 2.0% (w/v). The result showed that the syneresis rate was stable up to 2% of agar concentration at low storage temperature, while gum Arabic in the concentration of >1% resulted in increasing syneresis rate. Ambient temperature storage increased the syneresis rate. This study showed that agar or gum Arabic was supporting the probiotication as good encapsulant. Moreover, it was suitable for stabilizing or gelling agent at 0.5%-1% concentration to produce black grass jelly as RTD.